2009
DOI: 10.1158/1055-9965.epi-09-0665
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Prostate Cancer Susceptibility Variants on Prostate-Specific Antigen Recurrence after Radical Prostatectomy

Abstract: Recent genomewide association studies have identified several prostate cancer susceptibility variants. However, the association between these variants and biochemical failure in prostate cancer patients receiving radical prostatectomy has not been determined. We systematically evaluated 20 prostate cancer-associated single-nucleotide polymorphisms in a cohort of 320 localized prostate cancer patients receiving radical prostatectomy. Each single-nucleotide polymorphism found to be associated with the recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 43 publications
0
70
1
Order By: Relevance
“…The study population was extended from our hospitalbased prostate cancer case-control study that has been described previously (11)(12)(13)(14)(15)(16). In brief, patients with diagnosed and pathologically confirmed prostate cancer were actively recruited from 3 medical centers in Taiwan: Kaohsiung Medical University Hospital, Kaohsiung Veterans General Hospital, and National Taiwan University Hospital.…”
Section: Patient Recruitment and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population was extended from our hospitalbased prostate cancer case-control study that has been described previously (11)(12)(13)(14)(15)(16). In brief, patients with diagnosed and pathologically confirmed prostate cancer were actively recruited from 3 medical centers in Taiwan: Kaohsiung Medical University Hospital, Kaohsiung Veterans General Hospital, and National Taiwan University Hospital.…”
Section: Patient Recruitment and Data Collectionmentioning
confidence: 99%
“…performed as described previously (14) using Sequenom iPLEX matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry technology at the National Genotyping Center, Academia Sinica, Taiwan. The average genotype call rate for these SNPs was 97.1% and the average concordance rate was 99.8% among 55 blind duplicated quality control samples.…”
Section: Translational Relevancementioning
confidence: 99%
“…[25][26][27] While the clinical implications of common genetic variants associated with PCa risk remain unclear, [28][29][30][31][32][33][34] deleterious germline mutations in both genes, BRCA1 and BRCA2, have been associated with more aggressive disease and poor clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, SNPs associated with disease progression are beginning to be identified. A recent study reported that two variants at 10q11 and one variant at 8q24 associated with susceptibility influence biochemical recurrence following radical prostatectomy [49]. Variants at 8q24 have been evaluated for risks of aggressiveness of prostate cancer based on age at onset, familial aggregation and tumor grades and stages.…”
Section: Discussionmentioning
confidence: 99%